Speaking Anxiety and Students' Self-Perceived Speaking Ability in Indonesian Language Learning at Senior High School - Kurniati Ladjambu; Asna Ntelu; Salam; Muslimin (Universitas Islam Negeri Palopo, 2026)
Formal speaking tasks in Indonesian language classrooms may still generate anxiety because students must organize ideas, speak before teachers and peers, avoid mistakes, and meet assessment expectations. This study examined the relationship between speaking anxiety and students’ self-perceived speaking ability in Indonesian language learning. Self-perceived speaking ability refers to students’ self-assessment of oral performance, not a direct teacher or researcher rating. Using a quantitative correlational design, the study involved 203 tenth-grade students at SMA Negeri 1 Gorontalo. Data were collected through two 1–5 Likert-scale questionnaires measuring speaking anxiety and self-perceived speaking ability. The instruments were reviewed by three expert validators and judged feasible with minor revision. Descriptive statistics, normality testing, and Spearman correlation were used to analyze the data. The results showed moderate speaking anxiety (M = 3.284, SD = 0.709) and moderate self-perceived speaking ability (M = 3.281, SD = 0.498). Spearman correlation indicated a significant negative association, rho = -0.335, 95% CI [-0.46, -0.20], p < 0.001. Thus, students with higher speaking anxiety tended to evaluate their speaking ability less positively. Because the study was correlational and self-reported, the findings should not be interpreted as causal evidence. The findings suggest the need for gradual speaking practice, clear assessment criteria, constructive feedback, and guided self-reflection.